Report on the 14th IFToMM 2015 World Congress - Wojnarowski, Józef (Zielona Góra: Uniwersytet Zielonogórski)
The Congress is held every 4 years, the 13th IFToMM2011 WORLD CONGRESS was held in Guanajuato, Mexico, 2011. It is the largest conference for the promotion of mechanism and machine science. It is a special occasion and a discussion forum for Researchers, Scholars and PhD Students with interests in the theory and practice of mechanism and machine science - to address new ideas, share solutions, experience, and discuss future research developments.
Keywords: biomechanics; elasticity; plasticity; vibrations; mechanics of structures; mechatronics; plates & shells; magnetohydrodynamics; rheology; thermodynamics; tribology; fluid dynamics